Evaluating the causal effects of foreign acquisition on domestic skilled and unskilled wages - Sourafel Girma; Holger Görg (Institute for the Study of Labor (IZA), 2003)
This paper investigates the effects of the takeover of a domestic establishment by foreign owners on the domestic target?s development of wages for skilled and unskilled workers. We pay particular attention to identifying the causal effect, using a propensity score matching approach combined with a difference-in-differences estimator, and differences in post acquisition effects depending on the nationality of the acquirer. Our results suggest that there is substantial heterogeneity in the post-acquisition wage effect depending on the nationality of the foreign acquirer, the industry in which the firms operate and the skill group of workers. In particular, we find that skilled workers, on average, experience a post acquisition increase in the wage rate following an acquisition by a US firm, while no such effect is discernible following acquisitions by EU or firms of other nationalities. For unskilled workers, there are positive post acquisition wage effects from take-overs by EU firms in the electronics industry and US firms in the food industry.
Keywords: F23; J31; 330; multinationals; acquisitions; wages; matching estimator; Übernahme; Direktinvestition; Multinationales Unternehmen; Lohnstruktur; Qualifikation; Ungelernte Arbeitskräfte; Schätzung; Großbritannien